2005
DOI: 10.1002/jat.1044
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sulphur mustard on human skin cell lines with differential agent sensitivity

Abstract: The ability of sulphur mustard (HD) to induce DNA damage places limits on the efficacy of approaches aimed at protecting human cells from the cytotoxic effects of HD using a variety of protective agents such as thiol-containing esters and protease inhibitors. In the present study, potential alternative strategies were investigated by examining the differential effects of HD on G361, SVK14, HaCaT and NCTC 2544 human skin cells. The G361 cell line was more resistant to the cytotoxic effects of HD than the NCTC, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 53 publications
2
12
1
Order By: Relevance
“…In the EpiDerm model, GSH liposomes showed significant protective effect even when applied 1 hour after CEES exposure. This observation further confirmed previous in vitro studies of CEES/HD toxicity, which have demonstrated that the antioxidants that reduce oxidative stress and prevent thiol depletion also attenuate CEES toxicity, whereas oxidants (hydrogen peroxide) [4] and agents that deplete intracellular glutathione (buthionine sulphoximine) [6, 42] sensitize human cell lines, in particular HaCaT [42], to CEES/HD toxicity. Thus, our study provides additional evidence of the critical role of oxidative stress in the pathogenesis of CEES/HD-induced injury in the skin.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the EpiDerm model, GSH liposomes showed significant protective effect even when applied 1 hour after CEES exposure. This observation further confirmed previous in vitro studies of CEES/HD toxicity, which have demonstrated that the antioxidants that reduce oxidative stress and prevent thiol depletion also attenuate CEES toxicity, whereas oxidants (hydrogen peroxide) [4] and agents that deplete intracellular glutathione (buthionine sulphoximine) [6, 42] sensitize human cell lines, in particular HaCaT [42], to CEES/HD toxicity. Thus, our study provides additional evidence of the critical role of oxidative stress in the pathogenesis of CEES/HD-induced injury in the skin.…”
Section: Discussionsupporting
confidence: 88%
“…However, this direct detoxification is possible only during a short time after the exposure, and other nucleophilic scavengers, for example, thiopurines [23] or exogenous peroxidases [44], are more effective in degrading of HD or CEES. Nevertheless, antioxidants and antioxidant liposomes have shown a great potential in preventive treatment of CEES/HD toxicity [3–5, 9, 10, 20, 21, 26, 34, 42, 4548]. In addition, it is well known that mammalian skin cells exposed to CEES/HD release proinflammatory cytokines [27, 28, 37, 49] and other immune stimulators [50].…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests that the protective effect of NAC against CEES-caused toxicity occurs in part through an increase in GSH levels, and the other mechanisms could be related to its activity as a strong ROS scavenger; NAC is also known to act via the nuclear factor-B pathway and inhibit prostaglandin synthesis apart from being a GSH precursor (Atkins et al, 2000;Arfsten et al, 2007). CEES-induced depletion of GSH and generation of ROS have been shown in human lymphocytes that induce cell death and in human skin cells where treatment with GSHdepleting agent BSO showed an increased toxicity to HD (Han et al, 2004;Simpson and Lindsay, 2005). In the present study, we also observed that BSO pretreatment to both the skin epidermal cells caused an increase in CEES-caused toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…NCTC2544 cells are known to have inducible Phase I and Phase II detoxication activities (20, 21) and have previously been used for studies of sulfur mustard toxicity (22). The medium used for exposure to the alkyl mustards was modified to accommodate relatively high concentrations of the potential scavenger, DTP, which is not readily soluble in water, phosphate buffered saline or DMEM.…”
Section: Methodsmentioning
confidence: 99%